De(s)colonize the look: images in teaching visual arts (Revista Apotheke, 2025)
The historical and cultural panorama of Latin America, whose roots are sustained in colonization and slavery, implies the construction of colonized looks, not only on the visualities that permeate us, but also on how our episteme has been secularly constructed within the dominant parameters. Based on this, this article builds bridges between the de(s)colonial perspective and visual culture studies with the aim of discussing the difficulties and possibilities of working with images in contemporary visual arts teaching. As our era is marked by ocularcentrism and the coloniality of power, it is understood that it is necessary to question who has the right to look and how the colonized looks operates, in order to provoke fissures so that the de(s)colonization of the looks of both teachers and students becomes possible. The action of de(s)colonizing the look enables us to confront the legitimacy of the fabrication of dominant narratives, opening up space for listening to and constructing other stories and narratives that resist the patterns that feed Eurocentric hegemony. Finally, we explain how and which images are viable to use in the classroom in favor of continuous movements towards the de(s)colonization of ways of seeing.
Keywords: art education; descoloniality; insurgent knowledge; visuality